THE IJUK NGANTEN TRADITION OF SRATUREJO VILLAGE AS AN INTANGIBLE CULTURAL HERITAGE SUSTAINED WITHIN THE COMMUNITY - Anwari, Ikhsan Rosyid Mujahidul; Rusnalasari, Zulidyana Dwi (Acitya Wisesa: Journal of Multidisciplinary Research, 2025)
The Ijuk Nganten tradition is a form of intangible cultural heritage that continues to be preserved by the people of Sraturejo Village, Baureno District, Bojonegoro Regency, East Java. This ritual involves the symbolic cleansing of newlywed couples by washing their hands, faces, and feet at the sacred site known as Sumur Nganten (Bridal Well), followed by prayers for blessings, fertility, and household harmony. Although performed in a simple manner, the ritual holds deep cultural and spiritual meaning, rooted in local oral traditions and communal belief systems. This study employs the historical method, beginning with heuristic investigation through data collection from local oral sources—including village elders and cultural custodians—as well as limited written documents and popular media. The gathered sources were then subjected to source criticism, interpretative analysis, and synthesized through historiographical construction to explore the socio-cultural and historical functions of the ritual. The findings suggest that Ijuk Nganten originated from a collective memory involving the legendary figure Akuwu Lembu Amisena and his consort Nyi Lebdasari, who underwent ritual purification at the site after reclaiming political authority during the Singhasari–Majapahit era. Today, the tradition serves not only a spiritual purpose but also reinforces environmental ethics, ancestral veneration, and communal identity. It remains a vital cultural expression, consistently practiced even by residents who have migrated outside the region, demonstrating its enduring significance amid social transformation.